Lincoln, Seward, and US Foreign Relations in the Civil War Era - Fry, Joseph A., 1947- (Book collections on Project MUSE., 2019)
"In Lincoln, Seward, and U.S. Foreign Relations, 1861-1869, Joseph A. Fry proposes to examine this crucial partnership and its legacy. Despite differences in upbringing, personality, and social status, Lincoln became much closer personally and professionally to Seward than to any other member of his cabinet. Seward shared Lincoln's adamant belief that the institution of slavery fatally impeded the country's ability to promote American values and influence abroad. They both advanced preservation of the Union as ultimate standard for foreign policy decisions, and, by forestalling European intervention in the Civil War, their actions were critical to the North's victory and resulting reunification of the states. Lincoln reinforced Seward's conviction that future empires would be based on international commerce, especially in the Pacific region, and that the construction of a transcontinental railroad and interoceanic canal, along with acquisition of strategic island outposts, would be essential to dominating world trade. After Lincoln's death, Seward served as secretary of state to President Andrew Johnson, and during his tenure, he not only skillfully navigated war-related issues such as the French intervention in Mexico and claims derived from Confederate ship building in Great Britain, he also acquired Alaska, one of the last North American additions to the ascendant American empire. Their policies provided the bridge between the nation's prewar emphasis on territorial acquisition and the great postwar pursuit of commercial markets abroad. Together, Lincoln and Seward formulated a remarkably prescient vision of late nineteenth-century U.S. imperial expansion"--